20D-dynamic representation of protein sequences - Czerniecka, Agata; Bielinska-Waz, Dorota; Waz, Piotr; Clark, Timothy (Genomics, 2016)
A new method of comparison of protein sequences has been formulated. The sequence of amino acids is represented by a set of point masses in a 20D space. The distribution of points in the space is obtained by applying the method of a walk in the 20D space. Projections of the 20D representation into 2D or 3D spaces illustrate the distribution of particular amino acids along the sequence. 20D moments of inertia are proposed as new descriptors of protein sequences. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Similarity/dissimilarity analysis of protein sequences; Descriptors; Alignment-free methods; Moments of inertia